Teachers' participation in the administration of public general high schools in Bulacan - Domingo, Emilio Sinaguinan 1918- ([Quezon City s.n.], 1967)
This study determined the extent of participation of teachers in the administration of three public general high schools in Bulacan and the extent to which administrators allow teachers' participation along the eight areas of administration.
Thesis (M.Ed.)--Univesity of the Philippines
Keywords: School supervision, Secondary